Preliminary Medical Studies of Electrocardiograph on Nanosensors; Applied Mechanics and Materials; Vol. 770 : Urgent Problems of Up-to-Date Mechanical Engineering - Grigoriev M. G. Mikhail Georgievich (Mechatronics, Automation and Control, 2015)
Title screen